Evaluation of the safety and immunomodulatory effects of sargramostim in a randomized, double-blind phase 1 clinical Parkinson’s disease trial - Howard E. Gendelman (Nature Portfolio, 2017)
Immune modulation: translating the benefits The immune system modulating drug sargramostim shows promising results in a small clinical trial with Parkinson’s disease (PD) patients. Previous studies have shown that sargramostim increases the number of regulatory T cells, attenuates immune responses, and confers neuroprotection in animal models of neurodegenerative disease. To determine whether these findings translate to humans, Howard E. Gendelman at the University of Nebraska Medical Center, USA, and colleagues examined the effects of sargramostim in 20 patients with PD. Despite the high number of mild to moderate reported adverse events, the drug was generally well tolerated and led to an increase in regulatory T cell number and activity. Moreover, preliminary assessments after 6 and 8 weeks of treatment suggested an overall improvement in the motor skills of patients that received the drug compared with those that received a placebo.